Popular Declinism and Racial Politics in the Age of Consensus: The Midlands, c. 1958-81 - Noble, William (2024)
This thesis uses four local case studies to examine the links between popular declinism and discourses of ‘race’ and immigration in the Midlands in the period c. 1958-81: Nottingham c. 1958 (around the time of the ‘race riots’), Smethwick c. 1959-64 (charting the growth of political racism in the town culminating in Peter Griffiths’ 1964 general election victory), Wolverhampton c. 1967-74 (the local background and reactions to local MP Enoch Powell’s ‘rivers of blood’ speech), and Leicester c. 1972-81 (examining reactions to the arrival of Ugandan Asian evacuees in 1972 and the rise and fall of the National Front’s popularity). Local press sources are heavily utilised, along with correspondence, the national press, film materials from the Media Archive for Central England, and contemporary popular and academic publications.